HuR in pheochromocytomas and paragangliomas – overexpression in verified malignant tumors. Issue 9 (30th June 2016) - Leijon, Helena; Salmenkivi, Kaisa; Heiskanen, Ilkka; Hagström, Jaana; Louhimo, Johanna; Heikkilä, Päivi; Ristimäki, Ari; Paavonen, Timo; Metso, Saara; Mäenpää, Hanna; Haglund, Caj; Arola, Johanna
Abstract : Pheochromocytomas and paragangliomas are rare, neural crest‐originating, neuroendocrine tumors. HuR is an mRNA‐binding protein of the ELAV/Hu‐protein family, which participates in posttranscriptional regulation of many cancer‐associated genes. HuR expression has been connected with aggressive behavior of several malignancies. Cyclooxygenase‐2 (COX‐2) is also expressed in several malignant tumors, and its expression is regulated by HuR. Tissue microarray of 153 primary pheochromocytomas and paragangliomas was investigated for the expression of HuR and COX‐2 proteins by immunohistochemistry using two different HuR antibodies (HuR19F12 and HuR3A). In these tumors, the expression of both intranuclear and cytoplasmic HuR was detectable. Increased cytoplasmic HuR expression was significantly associated with metastatic tumors. Increased COX‐2 and MIB‐1 expression also was associated with metastatic potential, and moreover, HuR and COX‐2 expression correlated with each other. Our data suggest that increased expression of HuR protein is associated with metastatic potential of paragangliomas and pheochromocytomas, and COX‐2 seems to be a target of HuR.